Programa educativo para el mejoramiento de la producción de textos descriptivos en estudiantes del segundo grado de educación secundaria Institución Educativa Mariscal Oscar R. Benavides, Iquitos 2023 - Vasquez Rengifo de Avellaneda, Sara (2025)
The purpose of the research carried out was to evaluate the effect of an educational program on the production of descriptive texts in second-year secondary school students of the Mariscal Oscar R. Benavides school in Iquitos during the year 2023. A quasi-experimental evaluative approach was adopted, intentionally selecting to 67 students (34 belonging to the experimental group and 33 to the control group) with informed consent. A specific rubric was used to assess the writing of descriptive texts. The initial data showed similar levels in both groups (GE=11.52 and CG=11.54 points, on a 'Process' scale). After the intervention, the experimental group outperformed the control group, reaching an average of 17.69 points ('Predicted Achievement') compared to 12.72 points for the control group, which represents an improvement of 4.97 points. The statistical analysis using the Mann Whitney U test of the five dimensions evaluated indicated a significant improvement in presentation, coherence, cohesion, adequacy, and grammar and spelling in the experimental group (p-values of 0.000; 0.000; 0.001; 0.000; and 0.002 respectively), thus validating the five specific hypotheses (p<0.05).